Improving Student Motivation In Phyisical Education Learning In SMP Negeri 1 2 Ã— 11 Kayutanam - Arif Pribadi; Defri, Defri; Kadrisam, Rahmat (Jurnal Guru Peneliti Professional, 2019)
The problem of this research is the low desire of children in carrying out learning activities of Physical Education for Health and Recreation (PJOK) at SMP Negeri 1 2x11 Kayutanam, Padang Pariaman Regency, possibly caused by lack of student motivation, lack of discipline in students participating in PJOK learning, not serious, not enthusiastic, lacking diligent, less creative when given lessons in the form of games. This type of research is descriptive, conducted from February to March 2018. The population of this study were students of SMP Negeri 1 2x11 Kayutanam, Padang Pariaman Regency, consisting of VII, VIII and IX, totaling 391 people. Sampling research is 20% of the population with random sampling technique as many as 50 people. The data was collected through a questionnaire instrument (questionnaire) with a Likert scale. Based on data analysis, the results of the study found that out of 50 respondents of SMP Negeri 1 2x11 Kayutanam, Padang Pariaman Regency, only 8 people (16%) were in very good category, 8 people (16%) were in good category, 20 0 (40%) were in moderate category, 12 people (24%) were in the poor category, there were even 2 people (4%) in the poor category. Thus, this means that there is still low student motivation in learning PJOK at SMP Negeri 1 2x11 Kayutanam, Padang Pariaman Regency.